Viability of a national unemployment insurance Savings Account Scheme in Kenya - Oloo, Bill Michael Nandwa (Strathmore University, 2014)
according to Crotty (2009), the Global Financial and Economic Crisis of the year 2008 was one of the worse economic disasters in the recent history with the exception of the Great Depression. Businesses, persons and nations alike were significantly shaken by the massive and sudden decline in economic activity which fundamentally changed perception of the roles of different players in the gl0obal economy.
Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Business Science Actuarial Science at Strathmore University
Keywords: Viability; National unemployment; Insurance; Savings Account Scheme